Seccure Zero-Touch Bootstrapping of IoT devices using Blockchain Technologies - Bandyopadhyay, Ushana (My University, 2023)
The Internet of Things (IoT) is a rapidly growing field that has found applications in various areas. Before an IoT device can be used, it needs to be bootstrapped. Bootstrapping configures the device with the credentials to connect to its user's network and communicate with other devices on the same network. Additionally, bootstrapping is an essential foundation for the security of the IoT network and its operation. Therefore, ensuring that the correct device connects to the correct network is crucial during bootstrapping. However, the bootstrapping process should also be user-friendly to promote widespread adoption and reduce the risk of errors caused during manual user bootstrapping. Several companies have introduced Zero-Touch Bootstrapping (ZTB) mechanisms to address these requirements. In ZTB, all the user needs to do is power on their newly bought IoT device, which automatically gets bootstrapped to their IoT network. However, the currently available ZTB mechanisms do not protect against misbinding. Misbinding occurs when a device connects to an unintended endpoint, potentially leading to malicious attacks. In this thesis, we propose a novel approach to ZTB where we leverage a blockchain-based network infrastructure to enhance its security. Our approach creates a unique bootstrapping network per device per user. The parameters for creating such a bootstrapping network are cryptographically shared between the device and its legitimate user. In summary, our approach securely transfers bootstrapping parameters, immutably records ownership transfers on the blockchain, and enables zero-touch bootstrapping based on verified credentials.
Keywords: IoT, security, misbinding, bootstrapping, blockchain, distributed ledger tech- nology